Potential phosphorus eutrophication mitigation strategy: Biochar carbon composition, thermal stability and pH influence phosphorus sorption. (August 2017) - Ngatia, L.W.; Hsieh, Y.P.; Nemours, D.; Fu, R.; Taylor, R.W.
Abstract: Phosphorus (P) eutrophication is a major pollution problem globally, with unprecedented amount of P emanating from agricultural sources. But little is known about the optimization of soil-biochar P sorption capacity. The study objective was to determine how biochar feedstocks and pyrolysis conditions influences carbon (C) thermal stability, C composition and pH and in turn influence the phosphorus sorption optimization. Biochar was produced from switchgrass, kudzu and Chinese tallow at 200, 300, 400, 500, 550, 650, 750 °C. Carbon thermal stability was determined by multi-element scanning thermal analysis (MESTA), C composition was determined using solid state 13 C NMR. Phosphorus sorption was determined using a mixture of 10% biochar and 90% sandy soil after incubation. Results indicate increased P sorption ( P < 0.0001) and decreased P availability ( P < 0.0001) with increasing biochar pyrolysis temperature. However, optimum P sorption was feedstock specific with switchgrass indicating P desorption between 200 and 550 °C. Phosphorus sorption was in the order of kudzu > switchgrass > Chinese tallow. Total C, C thermal stability, aromatic C and alkalinity increased with elevated pyrolysis temperature. Biochar alkalinity favored P sorption. There was a positive relationship between high thermal stable C and P sorption for Kudzu (r = 0.62; P = 0.0346) and Chinese tallow (r = 0.73; P = 0.0138). In conclusion, biochar has potential for P eutrophication mitigation, however, optimum biochar pyrolysis temperature for P sorption is feedstock specific and in some cases might be out of 300–500 °C temperature range commonly used for agronomic application. High thermal stable C dominated by aromatic C and alkaline pH seem to favor P sorption. Highlights: Increased biochar pyrolysis temperature led to increased high thermal stable carbon (C) and aromatic C. Elevated biochar pyrolysis temperature led to increased alkalinity and reduced phosphorus (P) availability. High thermal stable C dominated by aromatic C favored P sorption. Increased alkalinity dominated by Ca related positively with P sorption. Biochar has potential for mitigation of P eutrophication, when optimization point is identified.